Enseigner la lecture de l’écrit scientifique : revue de la littérature - Scheepers, Caroline (Studia Romanica Posnaniensia, 2025)
The contribution aims to draw up an inventory of the didactic recommendations made by French-speaking researchers on the teaching-learning of university reading, more specifically with regard to the reading of scientific writings with the aim of developing a dissertation.